1991
DOI: 10.1042/bj2750657
|View full text |Cite
|
Sign up to set email alerts
|

Purification, properties and influence of dietary copper on accumulation and functional activity of lysyl oxidase in rat skin

Abstract: Lysyl oxidase (protein-lysine 6-oxidase; EC 1.4.3.13) is a copper-containing enzyme that functions extracellularly and catalyses the oxidative deamination of peptidyl lysine. Lysyl oxidase was purified 150-175-fold from urea extracts of rat skin and uteri. Features of the enzyme were similar to those reported previously for lysyl oxidase obtained from rat aorta and bovine ligamenture. However, both approximately 40 and approximately 32 kDa polypeptide chains could be isolated from rat skin with apparent lysyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…By SDS-PAGE, recombinant human LO co-migrates with purified porcine LO with an apparent molecular mass of 32 kDa, in agreement with the apparent molecular mass of tissue-derived LO purified from several species [1,27,39]. The predicted molecular mass of the mature form of human LO, based on cDNA data, is 29 034 Da.…”
Section: Discussionsupporting
confidence: 67%
“…By SDS-PAGE, recombinant human LO co-migrates with purified porcine LO with an apparent molecular mass of 32 kDa, in agreement with the apparent molecular mass of tissue-derived LO purified from several species [1,27,39]. The predicted molecular mass of the mature form of human LO, based on cDNA data, is 29 034 Da.…”
Section: Discussionsupporting
confidence: 67%
“…Taken together these studies show that lysyl oxidase activity correlates well with the presence of the 32-kDa molecular form of lysyl oxidase, and not with the 50-kDa molecular form. It is of interest, however, that an active 45-kDa lysyl oxidase has been demonstrated in rat skin tissues (38).…”
Section: Extracellular Proteolytic Conversion Of Lysyl Oxidase Precurmentioning
confidence: 99%
“…'~J However, dyschondroplastic cartilage taken from broilers with homocysteine-induced T D had higher levels of collagen cross-links than did normal growth plate.lo9 Homocysteine can partially inhibit lysyl oxidase and not decrease collagen cross-linking, as found in rat skin studies in which lysyl oxidase was not the rate limiting factor in cross-link formation. 126 Other work showed that 1% homocysteine diet in rats caused a copper deficiency.I8 Because a copper deficiency will induce TD, it was hypothesized that a high homocysteine diet in broiler chicks could lead to a copper deficiency, which in turn causes TD. Although Vet Pathol 31:4, 1994 the broilers fed a high-homocysteine diet did not show signs of a copper deficiency (i.e., normal hematocrit and plasma copper concentration), addition of extra copper (250 mglkg) to the diet slightly but significantly reduced the severity of the lesion.…”
Section: Thiram and Antabusementioning
confidence: 99%